The cooperation between competition law enforcement authorities and public procurement authorities in the fight against bid rigging: The case of Vietnam - Tam, Tran Thanh (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2022)
The cooperation between competition law enforcement authorities and public procurement authorities has been widely recognized as an effective tool in detecting and preventing bid-rigging in the public procurement market. By employing empirical research in the form of in-depth interviews, this paper seeks to examine such cooperation in the Vietnamese context. The findings reveal that neither the Vietnamese public procurement agencies nor the Vietnamese competition authorities have successfully fulfilled their cooperative roles in fighting against bid-rigging. These findings provide valuable lessons for both Vietnamese and international policy-makers by emphasizing the need to examine the relationship between competition authorities and public procurement agencies towards effective anti-bid rigging enforcement.